CHARACTERISTIC OF PATIENTS WITH ORBITAL MENINGIOMA IN DR. KARIADI GENERAL HOSPITAL SEMARANG: Oral Presentation - Observational Research - Resident - Joko Satrio; Trilaksana Nugroho (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Meningioma is a neoplasm arising from arachnoid cap cells in the meninges. They can arise in the orbit as primary or secondary orbital meningioma. The characteristic and risk factors of orbital meningioma are essential to acknowledge. The aim of this study is to describe the characteristic and risk factors of patients with orbital meningioma in Dr.Kariadi Hospital. Methods : A retrospective study was held from the medical record of patients with a diagnosis of meningioma between January 2020-December 2022. The data of 58 patients included age, sex, duration of proptosis, length of proptosis, history of seizure, diplopia, history of contraceptive and trauma, RAPD, fundus examination, and CT-Scan results. Results : Most of the meningioma patients had female 98,27%, 70,68% in the fourth decade of life. The visual acuity of 25,88% of patients >6/18, and 22,41% were blind. Around 72,41% of proptosis occurred ≥ 1 year, 87,93% had signs of headache, only 1,72% underwent seizure, 8,62% had double vision, and 5,17% had a history of head trauma. Relative afferent pupillary defect occurred in 53,44% of the affected eye with 20,68% atrophic papil and 15,51% edema papil. CT-Scan result of 86,2% had sphenoid meningioma, and only 13,79% had optic sheath meningioma. Most of the patients (72,41%) used 3 months cycle hormonal injection contraceptive. Conclusion : The characteristic of orbital meningioma patients in DR.Kariadi Hospital were mostly women in the fourth decade of life, had proptosis and headache as primary signs and 3 months of intramuscular hormonal contraceptives were suspected to have a correlation.